Presentation and Management of a Giant Coronary Artery Aneurysm with a Fistula to the Right Ventricle - Nicholas Peterman; Bradley Kaptur; Naveed Adoni (Case Reports in Cardiology)
A 27-year-old female presented to our emergency department in ventricular tachycardia. During her workup, she was found to have an extremely rare giant aneurysmal left anterior descending artery (LAD) ending in a coronary fistula to the right ventricle (RV). After stabilization, a variety of treatment options were considered, as there is no standard first-line treatment.